PENENTU PEMILIHAN STRUKTUR MODAL PERUSAHAAN - Rahmawati, Setya Ayu; Lina, Hanifah Nada (TEMA, 2023)
In the economic uncertainty condition starting COVID-19 to interest rate increase caused by inflation cause company decrease their debt funding. However, 310 from 698 companies in Indonesia increase their debt funding. This study aims to find out what factors determine the company's capital structure amid economic concerns. This study was conducted by analyzing the annual financial statements of 59 companies that issued new bonds and IPOs during the period 2020 to 2022. The data were analyzed by using multiple linear regression. The results show that cash flow volatility is the most determining factor, and non-debt tax shield does not determine the choice of capital structure in times of economic uncertainy. Theoretically, the financial performance within this study proves the validity of pecking order theory, whereas, practically, recommending companies apply internal funding first in times of economic uncertainty.